2016
DOI: 10.1021/acsnano.6b04330
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Core–Shell Gold Nanoclusters: Aun (n = 42–50)

Abstract: Gold nanoclusters have attracted great attention in the past decade due to their remarkable size-dependent electronic, optical, and catalytic properties. However, the structures of large gold clusters are still not well-known because of the challenges in global structural searches. Here we report a joint photoelectron spectroscopy (PES) and theoretical study of the structural evolution of negatively charged core-shell gold nanoclusters (Au) for n = 42-50. Photoelectron spectra of size-selected Au clusters are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 57 publications
(90 reference statements)
0
51
0
Order By: Relevance
“…24 Notably, our previous joint experimental and theoretical studies have shown that Au 33 to Au 42 are all core−shell clusters with a highly symmetric four-atom tetrahedral core. [25][26][27] Au 46 and Au 47 are also core−shell clusters with a pyramidal fragment stacked with another truncated pyramid. 27 In this study, our focus is placed on the size range of Au n -(n = 55−60).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…24 Notably, our previous joint experimental and theoretical studies have shown that Au 33 to Au 42 are all core−shell clusters with a highly symmetric four-atom tetrahedral core. [25][26][27] Au 46 and Au 47 are also core−shell clusters with a pyramidal fragment stacked with another truncated pyramid. 27 In this study, our focus is placed on the size range of Au n -(n = 55−60).…”
mentioning
confidence: 99%
“…[25][26][27] Au 46 and Au 47 are also core−shell clusters with a pyramidal fragment stacked with another truncated pyramid. 27 In this study, our focus is placed on the size range of Au n -(n = 55−60). We use the unbiased basin-hopping global optimization method combined with density-functional theory (DFT) optimization 28,30 to obtain a much larger population of low-energy isomers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such clusters are frequently found to be very stable despite their low symmetry. [34][35][36] Their non-trivial geometries however make them challenging targets for traditional MP computational strategies, which depend heavily on symmetry to reduce the complexity of the system and to keep the mental and computational burden tractable. For large clusters we can also relax multiple shells of atoms, thus allowing us to accurately capture most of the relaxation effects.…”
Section: Discussionmentioning
confidence: 99%